Eva and the New Owl: Owl Diaries #4 - Elliott, Rebecca (New York, NY : Branches/Scholastic Inc., 2016)
Eva wants to be friends with Hailey, the new owl in her class, but when Hailey seems to prefer Lucy's company, Eva starts to feel left out, and even a little jealous of her best friend.
Keywords: Owls -- Juvenile fiction; Best friends -- Juvenile fiction; Jealousy -- Juvenile fiction; Elementary schools -- Juvenile fiction; Diaries -- Juvenile fiction; Schools -- Fiction; Owls -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Jealousy -- Fiction; Diaries -- Fiction